Transmissive solar sailing - Thompson, Samuel (2025)
Uniquely, solar sails are a means of accelerating a spacecraft via ambient space radiation rather than onboard propellant. In principle, this allows for continuous acceleration, and for the attaining of higher velocities than a reaction engine may achieve. These sails are also amongst the most sustainable orbit control systems, being associated with reduced satellite weight, mission cost and space debris footprint. However, they also have weaknesses that constrain how and where they can be used --- most notably, their poor performance in low Earth orbit (LEO), where the majority of satellite missions occur. Transmissive solar sails may mitigate these weaknesses and thereby promote the broader adoption of solar sails. Advocating for this future, this thesis seeks to collate and expand the existing literature pertaining to these sails across three core domains: orbital dynamics, optical design, and manufacturing processes.